2004
DOI: 10.1016/j.ehj.2004.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between C-reactive protein concentrations during glucocorticoid therapy and recurrent atrial fibrillation

Abstract: CRP concentration is a risk factor for recurrent and permanent AF. Methylprednisolone successfully prevents recurrent and permanent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0
15

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(172 citation statements)
references
References 19 publications
3
154
0
15
Order By: Relevance
“…This is indicative of an important role of sustained inflammatory process and validation of these observations in patients with distinct and homogeneous cardiac substrates is necessary. Furthermore, our findings are suggestive of a potential therapeutic benefit, after an aggressive anti-inflammatory treatment, for example with anti-inflammatory agents, 19 involving the improvement of AF cardioversion outcome and the reduction of AF recurrence rate in patients with arterial hypertension. The risks and benefits of such an approach should be further studied in carefully designed clinical trials.…”
Section: Study Limitationsmentioning
confidence: 87%
See 3 more Smart Citations
“…This is indicative of an important role of sustained inflammatory process and validation of these observations in patients with distinct and homogeneous cardiac substrates is necessary. Furthermore, our findings are suggestive of a potential therapeutic benefit, after an aggressive anti-inflammatory treatment, for example with anti-inflammatory agents, 19 involving the improvement of AF cardioversion outcome and the reduction of AF recurrence rate in patients with arterial hypertension. The risks and benefits of such an approach should be further studied in carefully designed clinical trials.…”
Section: Study Limitationsmentioning
confidence: 87%
“…Recently, other similar studies that included patients with PAF have shown that pre-cardioversion CRP is an important predictor for cardioversion outcome and maintenance of sinus rhythm after successful cardioversion. 10,19 The usage of a non-ultrasensitive assay to measure CRP serum levels in these studies may have led to an overstatement of the importance of these associations. To further corroborate this, a recent meta-analysis investigating the role of CRP in restoration of sinus rhythm and AF recurrence revealed a great heterogeneity in the analysed studies and regarded differences in the used CRP assay as an important source for this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Эти дан-ные могут свидетельствовать об общей воспалительной реакции организма в ответ на частые пароксизмы ФП. Аналогичные результаты получены и во многих других исследованиях, посвященных изучению роли латентного воспаления в патогенезе указанного нарушения ритма сердца [21][22][23]. Таким образом, в работе показано, что в 20% случаев причиной «идиопатической» формы ФП может являться латентный лимфоцитарный или полиморфно-клеточный миокардит вирусной этиологии.…”
Section: Cи сазонова и соавтunclassified